Aircraft simulation and control - Zhao, Liang. (2009)
This dissertation aims at F-16 fighter to design controller and to make simulation for analyzing its performance under specific condition. Nonlinear plants model of F-16 derived from the kinematics and dynamics of aircraft is first given, which provides a necessary precondition for analyzing and researching. Since nonlinear plant is complex and hard to analyze directly and lots of well-rounded theories were developed for LTI systems, so this dissertation mainly concentrates on LTI analysis methods. A decoupled linearization model that consists of lateral motion and longitudinal motion expressed by respective Jacobian Matrices is available for this project. After linearization of nonlinear plant model at its equilibrium point, three kinds of control approaches are presented in this dissertation. They are classical Root Locus design method, modern LQR method and H infinity method respectively. These three methods have their own advantages and disadvantages in aircraft control fields. In addition to numerical simulation using Matlab, the Real-time simulation also is included in this project for comparing and testing the design results and controller performance. Dspace Real-time simulation system is an effective and powerful tool for aerospace and other control fields. With its convenient tools, Control Desk Standard, MLIB/MTRACE, and wide rang of I/O interface boards, the rapid control prototyping (RCP) and hardware-in-the-loop (HIL) functions are easy to realize.